Financial distress, psychological distress, and cost-related nonadherence among diabetic patients: Latent profile analysis - Le, Minh Hoang; Dao, Tran Nhat Phong; Hoang, Phi Phung; Trieu, Thanh Binh; Dorofeeva, Valeria Valeryevna; Tran, Van De (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Diabetes imposes a huge economic burden on individuals, their families, the national health system, and the economy as a whole. Research on financial distress has not yet been explored in the diabetic population in Vietnam. This study was conducted to determine the prevalence of financial distress and its associated demographic, psychological distress, and cost-related nonadherence factors in patients with diabetes.Methods: A cross-sectional study was conducted on 311 patients with diabetes attending the outpatient department of a public hospital in An Giang, Vietnam, from April 2025 to May 2025. Newly diagnosed, controlled, and ongoing-therapy patients were included and classified by current management into lifestyle modification, oral medications, or insulin therapy (alone or in combination). Latent Profile Analysis (LPA) was performed to classify patients with diabetes into their most likely group based on their financial distress profile.Results: LPA identified three latent profiles: none (13.5%), mild (56.3%), and moderate (30.2%) financial distress. The ROC analysis identified a score of 25.5 as the optimal threshold for distinguishing between none and mild/moderate financial distress, with a sensitivity of 100% and a specificity of 98.9%. Multinomial logistic regression analysis revealed that higher psychological distress, being a worker or public employee, and cost-related nonadherence were significantly associated with having mild or moderate financial distress.Conclusion: Psychological distress and cost-related nonadherence are factors influencing financial distress in patients with diabetes. Future interventions should target these factors to help reduce the level of financial distress in this population.